Measuring Customers Loyalty Through Satisfaction In E-Commerce: An Empirical Study On Tokopedia - Vania Tanlim; Tommy Setiawan Ruslim (Jurnal Manajemen, 2024)
This study aims to empirically examine the impact of e-service quality, e-commerce innovation, utilitarian value, and hedonic value on customer loyalty, with customer satisfaction as a mediating variable at Tokopedia. The research population consists of Tokopedia users in Jakarta. The sample for this study includes 252 participants selected through screening questions and collected online via Google Forms using judgmental sampling. The data is processed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate a positive and significant influence of e-service quality, e-commerce innovation, utilitarian value, and hedonic value on customer loyalty, both directly and indirectly, through the mediation of customer satisfaction.